Efficient Routing in Manets that Takes into Account Dropped Packets in Order to Conserve Energy - Fathima , Nausheen; Bari , Mohd Abdul; Sanjay, Sanjay (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Mobile ad hoc networks are wireless networks that do not have a central server but instead function as a dispersed, multi-hop system. These networks are also known as mesh networks. MANETs are distinct from typical networks in several important respects, including the absence of a centralized coordinator, the dynamic nature of the network design, and the restricted access to network resources. MANETs can communicate thanks to a wireless radio transmission; nevertheless, because these networks are not physically secured, security measures can be implemented on them. In addition, because peer-to-peer networks are decentralized, they are an easy target for malicious actors that use the internet. As a result, a security solution is necessary to cope with the numerous attacks that may be launched against MANETs. It is difficult to maintain the batteries of MANET nodes charged while they are being used since the nodes themselves have restricted access to energy supplies. Therefore, giving energy efficiency together with security is a significant necessity in a distributed environment; numerous energy-efficient protocols and security protocols have been devised for MANETs, but these approaches are not ideal for the mission-critical applications that run on MANETs. Therefore, we want a unified solution that is capable of simultaneously satisfying our requirements for energy and security. It is difficult to establish the best secure and efficient way of routing between the source and the destination since there is no infrastructure, the network is peer-to-peer, and there are resource limits. When it comes to MANETs, we demonstrate that energy efficiency is just as crucial as secure routing, and we analyze the most recent research that has been conducted on the subject. The bottleneck that is generated by rejecting packets at the intermediate node is one of the issues that must be addressed when creating a system to handle this issue. The other obstacle is the lack of confidence in security solutions provided by third parties. As a result, we proposed a safe and energy-efficient routing protocol as a means of effectively mitigating harmful behaviors at the routing layer by carefully considering the factors that contribute to packet loss. The authentication that is offered by the approach that we have developed makes use of chaotic maps, which are far easier to calculate than RSA and ECC, both of which may be solved in polynomial time with the assistance of an advisor.